A prática educativa através dos tempos: dos antigos aos pós-modernos - Fernanda Antônia Barbosa da Mota; Carmen Lúcia de Oliveira Cabral (EccoS – Revista Científica)
The objective in this work was to show the concept of educational practice of some authors from different historical ages and to introduce a possible concept of educational practice from Deleuze and Guattari. The theoretical supports that founded our study are: Jaeger (2001), Rousseau (2001), Dewey (1959), Vázquez (2007), Sacristán (2002), Deleuze e Guattari (1996, 2011), Deleuze, (2010) e Gallo (2008) among others. We note that Deleuze and Guattari are our principal theoretical base. After emphasized the meaning and the significance of different conceptions of educational practice in the theoretical perspectives of essentialism, romanticism, pragmatism, critical pedagogy and postmodernism, we build a concept of educational practice based on the Deleuze and Guattari ́s ideas from which we reviewed our concept of educational practice.